AN INVENTORY MODEL FOR EXPONENTIAL TIME- SENSITIVE DEMAND AND PARABOLIC TIME LINKED HOLDING COST UNDER INFLATION AND SHORTAGES WITH SALVAGE VALUE - S.R.Singh, Monika Rani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In present paper, we established economic order quantity model for decaying items. Additionally,exponential time linked demand with time changeable parabolic holding cost. Shortages are acceptable and partially backlogged. Inflation is considered in this model. A mathematical model is developed for optimize the minimum total cost. Sensitivity analysis is completed to show the effect of changes in the constraints on the optimum solution. Keywords: Deterioration, Shortages, Parabolic holding cost, Inflation, exponential demand, Salvage value